Экономические проблемы управления качеством продукции в АПК - Семенов Сергей Николаевич (Наука, 1989)
Экземпляры: КХ (20100909) / Инвентарный номер: 942429 / Цена: 2.00 / Сис.шифр: 65.9(2)32-82 / Авт.знак: Э 40 / ГРНТИ: 68 / ББК: 65.32-82